Penerapan model Contextual Teaching and Learning berdasarkan tahap kognitif siswa pada pembelajaran Bahasa Arab - Kafahulloh, Muhammad (TA`DIBUNA, 2024)
This research aims to see whether some differences or interactions occur in Arabic language learning by applying the Contextual Teaching and Learning model based on the cognitive stage of students who are still at the concrete, transitional, or formal thinking stage. This research was carried out at Roudlotul Ulum Middle School with a quantitative research approach and used survey methods and Two Way ANOVA test analysis to see the relationship between Arabic language learning outcomes, learning models, and students' cognitive levels on concrete, transitional, and formal thinking criteria in class VIII A, B, and C as many as 23, 25, and 22 students. In this research, it was found that there were no differences in Arabic language learning outcomes based on learning models using Contextual Teaching and Learning and the application of conventional-based learning, as well as based on students' cognitive levels in formal, transitional, and concrete categories, but there was no interaction between learning models and students' cognitive levels. in determining Arabic language learning outcomes.   Abstrak Penelitian ini bertujuan untuk melihat ada tidaknya perbedaan maupun interaksi yang terjadi pada pembelajaran bahasa arab dengan penerapan model Contextual Teaching and Learning berdasarkan tahap kognisi peserta didik yang masih berada pada tahap berpikir konkret, transisi, maupun formal. Penelitian ini dilaksanakan di SMP Roudlotul Ulum dengan pendekatan penelitian kuantitatif dan menggunakan metode survei dan analisis uji Two Way ANOVA untuk melihat keterkaitan antara hasil belajar bahasa arab, model pembelajaran, dan tingkat kognitif siswa pada kriteria berpikir konkret, transisi, dan formal pada kelas VIII A, B, dan C sebanyak 23, 25, dan 22 siswa. Pada penelitian ini diperoleh bahwa tidak adanya perbedaan hasil belajar bahasa arab berdasarkan model pembelajaran menggunakan Contextual Teaching and Learning dan penerapan pembelajaran berbasis konvensional, serta berdasarkan tingkat kognitif siswa pada kategori formal, transisi, dan konkret, namun tidak terdapat interaksi model pembelajaran dan tingkat kognitif siswa dalam menentukan hasil belajar bahasa arab.